THE DEVELOPMENT OF ELECTRONICS COMIC BOOK ON RESEARCH DESIGN TOPIC - Chotkunakitti, Phatnatcha; Suksanguan, Wanrudee; Treammeerit, Napaporn (Journal of MCU Nakhondhat, 2023)
The objective of the research was to develop the electronic book (e-Book) and to assess learning achievement of students studying through the developed e-book, titled Research Design. This research was a quasi –experimental research by comparing the pre-test and post–test score of the student, and to evaluate the satisfaction of the learners in studying by e-book. The samples of this research were the fourth-year students, academic year 2021, of accounting faculty, Rangsit University, chosen by volunteer sampling, totally 39 students. Research instruments consisted of the e-book developed by the researcher, the pre-test and post-test form and the student’s satisfaction questionnaire on using the E-book. The statistics used in the study consisted of mean, standard deviation and paired t-statistics. The results from the study showed that the e-book consisted of content, alphabet, images, animation, and sound. For the learning achievement test by analyzing the paired t-statistical values, it was found that the scores from the test after studying with e-books were higher than the scores from the pre-study test, statistically significant level of 0.001. Therefore, it can be concluded that the students' learning achievement improved after learning through e-books. When considering the standard deviation, it was found that the standard deviation of the post-test scores was lower than the pre-test scores. It was shown that electronic books may help students with high and low performances to develop knowledge similarly. In addition, from the analysis of the mean scores of students' satisfaction toward e-books, it was found that overall students' satisfaction toward e-book was at a highest level.